Konflikte um Wahrheit (Nomos Verlagsgesellschaft mbH & Co. KG, 2024)
"Conflicts over Truth" brings together contributions presented at the first conference of the Young Network for Legal History, which took place at the MPI for Legal History and Legal Theory in Frankfurt in June 2023. The theme of the conference offered young scholars from Germany, Austria and Switzerland the opportunity to discuss their research on legal historical methodology, history of procedural law, history of science and ancient legal history. The contributions analyse claims about "truth" made in different contexts and discuss, among other things, approaches to judicial practice, "alternative facts" in antiquity, or interpreting legal historical sources. The volume also provides insights into current research projects.